A New Organizational and Study Skills Intervention for College Students with ADHD. Issue 2 (May 2022) - Hartung, Cynthia M.; Canu, Will H.; Serrano, Judah W.; Vasko, John M.; Stevens, Anne E.; Abu-Ramadan, Tamara M.; Bodalski, Elizabeth A.; Neger, Emily N.; Bridges, Rachel M.; Gleason, LaDonna L.; Anzalone, Christopher; Flory, Kate
Highlights: College poses difficulties for students with ADHD, but few specific treatments exist. This paper documents the results of an intervention for college students with ADHD. The focus is on organization, time management, and planning (OTMP) skills. Thirty participants completed six group and two individual treatment sessions. Post-treatment, they reported high satisfaction, and improved attention and OTMP. Abstract: The transition to college can be very challenging for individuals with ADHD. Increased task and life demands happen in tandem with deficits in time management, study skills and habits, and delaying rewards to achieve longer-term goals. Cognitive-behavioral treatment (CBT) holds promise for targeting these and related challenges. Psychosocial interventions exist for the general population of adults with ADHD, but not college students. Importantly, an intervention designed for college students should be manageable in terms of time and cost. We developed such an intervention specifically for college students with ADHD; organizational, time management, and planning (OTMP) skills were the focus of this largely behavioral treatment, as these most directly relate to the executive function deficits characteristic of ADHD and to the demands of college. Academic study skills and psychoeducation regarding ADHD and medication management were also included. The intervention was tested with 30 undergraduate, post-baccalaureate, and graduate students (57% biological males; M age 22.6; 83.3% White/Non-Hispanic) from two public universities in the U.S. Participants completed a battery of self-report measures of ADHD symptoms, impairment, and OTMP skills pre- and post-treatment. Most participants reported a past diagnosis of ADHD ( n = 23; including possible comorbidity), with all others reporting at least 5 pre-treatment symptoms of inattention ( M for all participants = 6.3). The manualized intervention consisted of 6 group therapy sessions and 2 individual sessions. Results suggested that this new treatment has promise, with t -tests comparing pre- and post-intervention scores indicating significant improvements in inattention symptoms, total ADHD symptoms, self-concept impairment, total impairment, and use of organization, time management, and planning skills. In addition, participants generally reported satisfaction with the intervention and had a very high attendance rate. Future studies of this new intervention should include a randomized controlled trial, the collection of objective outcome measures, and a more diverse sample.